Vascular Remodeling Process in Pulmonary Arterial Hypertension, with Focus on miR‐204 and miR‐126 (2013 Grover Conference Series). (1st June 2014) - Potus, François; Graydon, Colin; Provencher, Steeve; Bonnet, Sébastien
Abstract : Pulmonary arterial hypertension (PAH) is a vascular remodeling disease characterized primarily by increased proliferation and resistance to apoptosis in distal pulmonary arteries. Previous literature has demonstrated that the transcription factors NFAT (nuclear factor of activated T cells) and HIF‐1α (hypoxia inducible factor 1α) are extensively involved in the pathogenesis of this disease and, more recently, has implicated STAT3 (signal transducer and activator of transcription 3) in their activation. Novel research shows that miR‐204, a microRNA recently found to be notably downregulated through induction of PARP‐1 (poly [ADP‐ribose] polymerase 1) by excessive DNA damage in PAH, inhibits activation of STAT3. Contemporary research also indicates systemic impairment of skeletal muscle microcirculation in PAH and attributes this to a debilitated vascular endothelial growth factor pathway resulting from reduced miR‐126 expression in endothelial cells. In this review, we focus on recent research implicating miR‐204 and miR‐126 in vascular remodeling processes, data that allow a better understanding of PAH molecular pathways and constitute a new hope for future therapy.